An ultrasonic scoring system to predict the prognosis of placenta accreta: A prospective cohort study. Issue 35 (August 2018) - Chong, Yiwen; Zhang, Aiqing; Wang, Yan; Chen, Yunshan; Zhao, Yangyu
Abstract : Abstract: To discuss the value of "self-made ultrasonic scoring system" in predicting the different types of placenta accreta, and for predicting its associated risk of bleeding and hysterectomy. A prospective study was performed in 137 patients who were suspiciously diagnosed with placenta accreta before delivery. All the patients were examined by the scoring system, and were classified into 3 groups according to their scores: score of ⩽5 as N1, ≥6 and ⩽9 as N2, and ≥10 as N3 groups. The accuracy and the Kappa values were calculated. Hemorrhage during the operation and the uterine resection rate were also compared. There were 73 patients in N1, 36 in N2, and 28 in N3 groups. The prediction accuracy rates were 87.6% (64/73) and 92.0% (25/28), respectively in groups 1 and 3. The Kappa value was 0.75\0.77 for the prediction accuracy rate. The median quantities of hemorrhage during the operation were 400[100, 2000] mL, 1200[300, 9000] mL, and 4000[800, 13, 000] mL, respectively. The uterine resection rates were 0.0%(0/73), 11.1%(4/36), and 39.3%(11/28), respectively. Comparison of hemorrhage and uterine resection rate among the 3 groups was significant ( P < .001). Among them, statistically significant differences in hemorrhage and uterine resection rate were observed in every 2 groups ( P < .05). These results suggested that self-made ultrasonic scoring system remained an effective diagnostic tool for assessing the types of placenta accreta, and predicted the associated bleeding risk, indicating the possibility of hysterectomy.